2020
DOI: 10.3390/su12208292
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to Climate Change in Semi-Arid Rural Areas: A Case of the Limpopo Basin Part of Botswana

Abstract: Climate change and anthropogenic pressure are increasingly modifying and interfering with ecosystem functions and limiting the delivery of ecosystem products, livelihoods, and adaptive response capacity in many developing countries. We identify measures by which local people in the semi-arid Limpopo Basin part of Botswana are responding to climate change and fluctuations in ecosystem products and examine socio-economic attributes of households influencing their adoption and discuss their adequacy. Our study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…A compelling illustration comes from a study by [9], which reported an increasing frequency and intensity of droughts in the Limpopo Basin in recent years, further limiting rainfed crop production. Several other studies have corroborated this trend, indicating a heightened dependence on forest products as a coping mechanism during drought years compared to other years [4,10,11].…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…A compelling illustration comes from a study by [9], which reported an increasing frequency and intensity of droughts in the Limpopo Basin in recent years, further limiting rainfed crop production. Several other studies have corroborated this trend, indicating a heightened dependence on forest products as a coping mechanism during drought years compared to other years [4,10,11].…”
Section: Introductionsupporting
confidence: 52%
“…Thus, we conclude that T&NTFPs in this study contributed significant cash income that is critical to financing household climate change adaptation initiatives. This is noteworthy considering the increasing precarity of rain-fed agriculture in semi-arid areas [11] and the limited off-farm livelihood opportunities in many rural areas. We also noted the potential threats to the sustainability of local forest products due to the increasing need for cash income driven by rising demand for forest products such as Mopane caterpillars and firewood and the seamless integration with distant urban markets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Government assistance (Maltou and Bahta 2019) and women empowerment (Maltitz and Bahta 2021) could help build smallholder livestock farmers' resilience in South Africa and is recommended as a way of improving resilience among female livestock farmers. Mugari et al (2020) reckons that knowledge of the factors which affect decisions concerning adaptation is critical towards developing resilience in semi-arid rural areas of Botswana.…”
Section: Cluster 3 (Blue): Food Security-sustainability-resilience Nexusmentioning
confidence: 99%
“…Despite the importance of livestock in the national economy and the changing climate is a worldwide concern, the literature on climate and agriculture, particularly livestock production in Botswana, is scant. Most studies tend to focus on farmers' perceptions of climate change and mitigation strategies [52][53][54][55][56]. There are a few notable studies that have examined the relationship between climate and livestock production.…”
Section: Introductionmentioning
confidence: 99%